The Impact of Transformational Leadership on Employee Performance in Government Agencies - Safitri; Indah; Hartati (Economy, Business, Finance, Accounting & Management Journal, 2025)
This study aims to analyze the influence of transformational leadership on employee performance in government agencies. Transformational leadership is a leadership style that emphasizes a leader’s ability to provide inspiration, motivation, ideal influence, and individual attention to subordinates in order to enhance organizational effectiveness. The study employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to government agency employees who served as research respondents. Data analysis was conducted using inferential statistical techniques to test the relationship and influence between transformational leadership variables and employee performance. The results of the study indicate that transformational leadership has a positive and significant effect on employee performance. The higher the application of transformational leadership by leaders, the higher the level of employee performance, as evidenced by improvements in work quality, work quantity, timeliness, responsibility, and teamwork. These findings indicate that the application of transformational leadership can be an effective strategy for improving productivity and the quality of public services. Therefore, government agencies need to encourage the development of transformational leadership competencies at every managerial level to support the optimal achievement of organizational goal